The Free Trade Zone of Iquique and its impact on informal work of of border migrant women (Polis (Santiago), 2019)
The Free Trade Zone of Iquique has been a sustained engine of economic development in the Tarapacá region, in northern Chile. Since its creation, it has been a transit space for goods and people that connects Tarapacá with the West Central South America. In geographic terms, this space turns out to be key for circulation due to its border position. Therefore, it is an attractive niche for employment. What are the employment conditions that it provides to migrant women? From interviews conducted with migrant women working in the industrial zone of the Free Trade Zone, it is concluded that the job offer in this area is precarious and offers difficulties to perform administrative procedures that allow women to regularize their migratory status.
Keywords: Free Trade Zone; migration; feminization; employement; Tarapacá Region